If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + -10 = 10 + -4x Reorder the terms: -10 + 6x = 10 + -4x Solving -10 + 6x = 10 + -4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4x' to each side of the equation. -10 + 6x + 4x = 10 + -4x + 4x Combine like terms: 6x + 4x = 10x -10 + 10x = 10 + -4x + 4x Combine like terms: -4x + 4x = 0 -10 + 10x = 10 + 0 -10 + 10x = 10 Add '10' to each side of the equation. -10 + 10 + 10x = 10 + 10 Combine like terms: -10 + 10 = 0 0 + 10x = 10 + 10 10x = 10 + 10 Combine like terms: 10 + 10 = 20 10x = 20 Divide each side by '10'. x = 2 Simplifying x = 2
| 2x=-2/7 | | -1/18=m-5/9 | | -2/3+w=1/3 | | b/5=-3 | | k+3/7=85/84 | | a/-7=-6 | | k/-4=6 | | 31/9=k+4/9 | | b-3=-32/9 | | t-3/8=53/8 | | -6m=5/2 | | d-7/8=9/8 | | t+6=12 | | d-5=-14/3 | | -5/7=t-1 | | x-3/4=-27/4 | | d-1=-1/6 | | m-7/9=-1/36 | | k-2/7=-11/14 | | 3/10+b=7/10 | | w+2=13 | | b+3/7=-25/7 | | a/-3=-2/5 | | w/4=-1/7 | | n+1/2=-17/2 | | x-1/10=29/10 | | 2/3a=1/3 | | -1+x=-2/7 | | b-1/2=23/2 | | k-2/5=48/5 | | k-3=-7/2 | | a-4/7=-11/56 |